OP57 Endorsement of masculine norms and associations with suicidality among adolescent males. (3rd September 2019) - King, TL; Shields, M; Sojo, V; Daraganova, G; Currier, D; O'Neil, A; King, K; Milner, A
Abstract : Background: On many indicators of mental health, such as suicide, adolescent boys and young men fare worse than girls and young women of the same age. Traditional masculine-typed norms and behaviours have been associated with deleterious health outcomes, and among adult men, endorsement of certain masculine norms (such as self-reliance) has been associated with suicidal ideation and poorer mental health. While the examination of masculinity is a useful means of understanding health risks in men and boys, there has been little quantitative examination of this relationship, particularly among adolescents. This study aimed to examine associations between endorsement of masculine norms and suicidal ideation in a representative sample of Australian adolescents. Methods: Using data from the Australian Longitudinal Study on Male Health, this study examined associations between specific masculine constructs and suicidal ideation among 826 Australian boys/young men aged 15–18 years at baseline. Masculine norms were measured in Wave 1, using the Conformity to Masculine Norms Inventory (CMNI-22). Suicidal ideation was a single item from the Patient Health Questionnaire (PHQ9), and was measured in Wave 2 (when participants were 17–20 years of age). Logistic regression analysis was conducted, adjusting for available confounders. Results: Results showed that after adjustment for parental education and area socio-economic position, greater conformity to violent norms (OR 1.23, 95%CI: 1.03–1.47) and self-reliance norms (OR 1.49, 95%CI: 1.15–1.70) were associated with higher risk of suicidal ideation. Greater conformity to norms regarding heterosexuality was associated with reduced risk of suicidal ideation (OR 0.80, 95%CI: 0.68–0.91). Conclusion: Among the adolescent males in this sample, we found that high conformity to norms of violence and self-reliance was associated with greater risk of suicidal ideation, while high conformity to norms of heterosexuality was associated with reduced suicidal ideation. Such results do not indicate that being heterosexual is protective but highlight the broader buffering effect of conforming to the masculine norm of heterosexuality. Maximising adolescent health is recognized as key to a sustainable, healthy and equitable future. These results suggest that conforming to certain masculine norms may be deleterious for adolescent male health and highlight the importance of presenting multiple ways of being a male. This is vital in shifting social norms toward a society that supports various, and varying forms of masculinity, particularly in terms of sexuality.